SOCIO-ECONOMIC IMPACT ANALYSIS OF DRAINAGE DEVELOPMENT: A CASE STUDY ON JAMIN GINTING STREET, TITI RANTAI SUBDISTRICT - Fajar Pramudya; Muhammad Husni Thamrin (Yayasan Wayan Marwan Pulungan, 2025)
This study examines the socio-economic impact of drainage development on Jalan Jamin Ginting, Titi Rante Village. Improperly planned or managed drainage projects can disrupt local livelihoods, employment opportunities, social interactions, and environmental conditions, negatively affecting the surrounding community. Using a qualitative descriptive approach, data was collected through interviews, observation, documentation, and literature study. The findings reveal that the drainage development has primarily had negative impacts on the community, including disruptions to livelihoods and social activities, as well as inadequate regulations, unqualified human resources, lack of institutional synergy, financial mismanagement, and outdated technology, all of which have hindered timely and effective implementation.